Prevalence of geriatric syndromes and associated factors in Iranian older adults with type 2 diabetes: A population-based correlational study - Mehdi Rahimi; Sarieh Poortaghi; Reza Negarandeh (Tehran University of Medical Sciences, 2024)
Background & Aim: Geriatric syndromes are known as a major obstacle in the treatment and care of older adults with diabetes. This study aimed to determine the prevalence of geriatric syndromes and associated factors in community-dwelling older adults with diabetes in the south of Tehran, Iran, in 2022. Methods & Materials: A population-based correlational study was conducted among 392 older adults with diabetes, covered by selected health centers in the south of Tehran, Iran, using the multistage sampling method. Persian forms of geriatric assessment tools were used, including Mini-Mental State Examination, Activities of Daily Living, Instrumental Activities of Daily Living, Mini Nutritional Assessment, and Geriatric Depression Scale. The obtained data were analyzed by descriptive and chi-square tests in SPSS-26. Results: The mean age of the participants was 69.5±6 years (63% female, 37% male). About 54.6% of the older adults with diabetes studied had three or more Geriatric syndromes. Polypharmacy was the most prevalent geriatric syndrome (76.5%). The number of geriatric syndromes had a significant association with female gender (p<0.001), lower education (p<0.001), loss of the spouse (p= 0.004), and lower-income (p=0.019). Also, with the increase in the number of diabetes comorbidities, the occurrence of all geriatric syndromes increased significantly (p<0.001). Conclusion: The prevalence of geriatric syndromes in older adults with diabetes in the south of Tehran is very high and warning. Due to the increasing population of older adults in Iran, policymakers and healthcare providers should take appropriate actions to confront the issue with a comprehensive understanding of the present condition.